Turkish armed forces - Lisec, Eckhard, 1944- (Wiesbaden)
154 sayfa, xvi sayfa resim, portre, çizim
Keywords: “The origins of the Turkish armed forces go back to the 3rd century B.C. Historically important they became when in 1453 they conquered Constantinople, made an end to the Byzantine Empire and founded the Ottoman Empire which dominated the Middle East, North Africa and great parts of the Balkans until middle of the 19th century. Then its decline began and at the end the Ottoman Empire was the “Sick Man“ on the Bosporus. World War I brought an end and in 1923 the Republic was founded by Mustafa Kemal (Atatürk). From then on the army was the guard of the Republic against external and internal forces. This study describes the details of these developments with focus on the development of the Turkish military. The author was an officer by profession and spent many years as NATO-staff in Turkey“ --